Estudo da composição corporal e volemia de pacientes em diálise peritoneal através da bioimpedância : avaliação da influência do líquido intraperitoneal e da relação com o estado nutricional - Lienert, Rafaela Siviero Caron (2013)
Background: Fluid overload (FO) is common in patients on PD and the combination with inadequate nutritional status causes increased mortality in peritoneal dialysis (PD) patient. Bioimpedance spectroscopy is a precise, sensitive and reliable tool for determining the fluid volume status and body composition of PD patients. The main aims of this study were: to compare body composition and volume variables, measured with the dialysis fluid inside the peritoneal cavity (CC) and after its drainage (EC), using the Body Composition Monitor (BCM); and to evaluate associations of the nutritional status and body composition of patients receiving PD, with their volume status. Methods: A cross-sectional study involving 37 stable adult patients (>18 years) on PD. A BCM report was used for the analysis of fluid status and body composition, and was conducted with both a CC and EC. Results: The study sample had the following characteristics: 62.5% female, 68.8% Caucasian, 75.0% on continuous ambulatory peritoneal dialysis (CAPD) and 25.0% on peritoneal dialysis automatized (APD). Evaluation of 32 patients showed no statistical difference between CC and EC in regard to overhydration (OH), total body water, extracellular water, intracellular water and their corrections for height and weight, lean tissue mass, fat tissue mass and their indices, adipose tissue mass, and body cell mass. Pearson's correlation coefficient of OH between CC and EC was r=0.989 (P<0.001). Bland-Altmann plot for OH full and OH empty had a line of bias of -9 mL and 95% limits of agreement from -603 to 585 ml. In another analysis with 37 patients serum albumin was higher in euvolemic (EV) patients (P=0.013), and the Subjective Global Assessment and Malnutrition Inflamation Score were higher in OH patients (P=0.002 and P=0.004, respectively). All hypertensive patients were diagnosed as OH. Several correlations were disclosed between nutritional markers and body composition markers and volemia. Conclusion: The presence of intraperitoneal fluid does not interferes with the evaluation of hydration status using BCM, or in the analysis of corporal composition - lean tissue mass, fat tissue mass, adipose tissue mass and their indices, suggesting that the BCM methodology can be applied in both conditions, with or without drainage of the dialysate solution. Besides the volume status of PD patients has a strong association with nutritional assessment variables. Consequently, a detailed evaluation of volume status should be part of a complete nutritional assessment, aiming an appropriate nutritional state.